Uterine artery pulsatility index improves prediction of methotrexate resistance in women with gestational trophoblastic neoplasia with FIGO score 5–6. Issue 8 (21st March 2013) - Sita‐Lumsden, A; Medani, H; Fisher, R; Harvey, R; Short, D; Sebire, N; Savage, P; Lim, A; Seckl, MJ; Agarwal, R
<x xml:space="preserve">Abstract</x> Objective The Uterine Artery Pulsatility Index (UAPI) is an ultrasound measure of tumour vascularity. In this study, we hypothesised that a UAPI ≤1 (high vascularity) would identify women with gestational trophoblastic neoplasia (GTN) at increased risk of resistance to first‐line single‐agent methotrexate (MTX‐R). Design Single‐centre cohort study. Setting Charing Cross Hospital, a UK national centre for the treatment of trophoblastic disease. Population All women with a GTN FIGO score 5–6 treated with methotrexate (n = 92), between 1999 and 2011, at Charing Cross Hospital. Methods UAPI was measured before the start of chemotherapy, and women were monitored for the development of MTX‐R. Main outcome measures Frequency of MTX‐R in women with UAPI ≤1 compared with UAPI >1. Results UAPI was measured before chemotherapy in 73 of 92 women with GTN FIGO score 5–6. UAPI ≤1 predicted MTX‐R independent of the FIGO score (hazard ratio 2.9, P = 0.04), with an absolute risk of MTX‐R in women with a UAPI ≤1 of 67% (95% CI 53–79%) compared with 42% (95% CI 24–61%) with a UAPI >1 (P = 0.036). Conclusion Our results suggest UAPI is an independent predictor of MTX‐R in women with FIGO 5–6 GTN.